2024
DOI: 10.1186/s13018-023-04465-2
|View full text |Cite
|
Sign up to set email alerts
|

Megaprosthetic replacement in complex distal humerus fractures in elderly patients: a case series

Matteo Caredda,
Luigi Cianni,
Andrea De Fazio
et al.

Abstract: Background Managing distal humeral fractures can be challenging for orthopedic surgeons. There are several treatment options for managing this type of fracture, and the treatment method for these fractures should be based on patient-related factors. In elderly patients with osteoporotic bone and severe comminution of the fracture, adequate fixation can be a major challenge for surgeons. The use of megaprosthesis has been recently proposed in traumatology as an alternative to osteosynthesis or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Modular or custom-made elbow megaprostheses have been recently proposed in traumatology as an alternative to osteosynthesis or conventional prosthesis for managing comminuted articular fractures in elderly patients with poor bone stock [ 35 ]. Casadei et al [ 20 ] showed that modular prosthesis could yield good functional outcomes in elbow reconstruction for both primary and metastatic lesions; nerve palsy is the most common complication but is often temporary and does not seem to affect ROM and postoperative function.…”
Section: Discussionmentioning
confidence: 99%
“…Modular or custom-made elbow megaprostheses have been recently proposed in traumatology as an alternative to osteosynthesis or conventional prosthesis for managing comminuted articular fractures in elderly patients with poor bone stock [ 35 ]. Casadei et al [ 20 ] showed that modular prosthesis could yield good functional outcomes in elbow reconstruction for both primary and metastatic lesions; nerve palsy is the most common complication but is often temporary and does not seem to affect ROM and postoperative function.…”
Section: Discussionmentioning
confidence: 99%